Precious Evanescence: The “Little Angels” by Chichico Alkmim through the Lens of Vladimir Jankélévitch - Salgado Gontijo, Clovis (Text Matters: A Journal of Literature, Theory and Culture, 2025)
This article establishes a dialogue between two distinct domains: the portraits of deceased infants—known in Brazil as anjinhos (“little angels”)—captured by the Brazilian photographer Chichico Alkmim (1886–1978) in the first decades of the 20th century in the region of Diamantina (Minas Gerais), and the thought of the French philosopher Vladimir Jankélévitch (1903–85), who deeply reflected on themes such as death, memory, transience, irreversibility, and innocence. The article is divided into two main sections, each with two subsections. The first section begins by contextualizing the conception of the anjinho in the popular and religious collective imagination of Minas Gerais, from colonial times to the early 20th century (1.1). It then introduces Chichico Alkmim’s biography and his particular approach to the anjinhos portraits (1.2). The second section shifts the focus to the project’s central aim, connecting cultural and historical implications, as well as artistic traits of this poignant photographic production to certain aspects of Jankélévitch’s work. Initially, this connection is explored through a negative approach (2.1), highlighting how the religious beliefs surrounding the anjinhos, the association between childhood and death, and postmortem photography contrast with Jankélévitch’s values and sensibility. The final subsection (2.2), however, delves into a point that might draw the philosopher closer to Chichico’s anjinhos portraits: the commitment (endowed with ontological and ethical implications) of attesting to a completed existence.